Pengaruh Penerapan Sistem Administrasi Perpajakan Modern Terhadap Kepatuhan Wajib Pajak (Students' Journal of Accounting and Banking, 2013)
Modern tax administration system is the implementation of modern tax administration system that experienced improvement or repair to both individuals and institutions to be more efficient, economical and fast. The objective of this research is to examine whether modernization in taxation administration system at Semarang Tax Office affects tax compliance. Type of this research is quantitative descriptive. The samples in this study were employees of a tax on KPP Pratama Semarang Barat dan KPP Pratama Semarang Timur. The sample size is determined with purposive sampling method. Survey method is applied with data collected through interview and questionnaire by using multiple regression analysis applied in data processing SPSS 16. The results of this study indicate that partial testing showed variable changes in organizational structure, change implementation services, IT service facilities that utilize no significant effect on tax compliance, while variable code employee has a significant impact on tax compliance, from the simultaneous testing showed that all the independent variables have a significant positive effect on the dependent variable.Keywords: modern tax administration system, taxpayer compliance.